SOCIAL ACTOR REPRESENTATION IN SOLOPOS CRIME NEWS DISCOURSE - Hendrastuti, Retno; Aji, Endro Nugroho Wasono; Okitasari, Indah; Maemunah, Emma (Widyaparwa, 2024)
The events of crimes in society receive big attention from mass media, as well as SOLOPOS, one of the biggest newspapers in Central Java. The mass media cannot be considered a neutral channel that reports the social actors in crime news. This study observes and researches the discourse of crime news in SOLOPOS, identifies how the newspaper represents the social actors in the discourse, and explores the representation. The discourse analysis of Theo van Leeuwen's model is used to find qualitative content analysis methods. This method tries to understand the message reflected in the representation of social actors in discourse. The results of the study showed that SOLOPOS uses a strategy of exclusion and inclusion. The exclusion strategies used were nomination and elimination of adverbial function. The inclusion discourse strategies used were differentiation, abstraction, categorization, identification, determination, assimilation, and association. The strategies were found in all parts of the text, those were in the title, lead, and news body. Furthermore, the exclusion strategy was found in reporting criminal cases of corruption which tried to exclude the actor or the perpetrators. Then, the inclusion strategy involved in almost a variety of cases that tried to expose the perpetrators. It means that SOLOPOS tend to display the perpetrators in their crime discourse presentation for the benefit of the victims.Peristiwa kejahatan di masyarakat mendapat perhatian besar dari media massa, begitu pula SOLOPOS, salah satu surat kabar terbesar di Jawa Tengah. Media massa tidak bisa dianggap sebagai saluran netral yang terkadang dalam pemberitaannya berpihak pada salah satu aktor sosial dalam wacana berita kriminal. Penelitian ini bertujuan  mengamati dan meneliti wacana berita kriminal pada media massa SOLOPOS, lebih spesifik mengenai mengetahui bagaimana surat kabar tersebut merepresentasikan aktor-aktor sosial dalam wacana yang diterbitkan. Untuk mengeksplorasi representasi tersebut digunakan analisis wacana model Theo van Leeuwen. Kemudian, metode penelitian kualitatif dipertahankan untuk menganalisis data, yaitu untuk memahami pesan yang tercermin dalam representasi aktor sosial dalam wacana. Hasil penelitian menunjukkan bahwa SOLOPOS dalam pemberitaannya menggunakan strategi eksklusi dan inklusi. Strategi eksklusi yang digunakan adalah nominasi dan eliminasi fungsi adverbial. Strategi wacana inklusi yang digunakan adalah diferensiasi, abstraksi, kategorisasi, identifikasi, determinasi, asimilasi, dan asosiasi. Strategi tersebut terdapat pada seluruh bagian teks, yaitu pada judul, lead, dan badan berita. Lebih lanjut, strategi eksklusi ditemukan dalam pemberitaan kasus pidana korupsi yang berusaha mengecualikan pelaku atau pelakunya. Kemudian, strategi inklusi terlibat dalam hampir berbagai kasus yang berusaha mengungkap pelakunya. Artinya, SOLOPOS cenderung menampilkan pelaku dalam penyajian wacana kejahatannya demi kepentingan korban.